Cognitive flexibility in internet addicts: fMRI evidence from difficult-to-easy and easy-to-difficult switching situations. - Dong, Guangheng; Lin, Xiao; Zhou, Hongli; Lu, Qilin (Addictive Behaviors, 2014)
Abstract: Internet addiction disorder (IAD) has raised widespread public health concerns. In this study, we explored the cognitive flexibility in IAD subjects using a color–word Stroop task. Behavioral and imaging data were collected from 15 IAD subjects (21.2±3.2years) and 15 healthy controls (HC, 22.1±3.6years). Group comparisons found that IAD subjects show higher superior temporal gyrus activations than healthy controls in switching (easy to difficult; difficult to easy) than in repeating trials. In addition, in difficult-to-easy situation, IAD subjects show higher brain activation in bilateral insula than healthy controls; in easy-to-difficult situation, IAD subjects show higher brain activation in bilateral precuneus than healthy controls. Correlations were also performed between behavioral performances and brain activities in relevant brain regions. Taken together, we concluded that IAD subjects engaged more endeavors in executive control and attention in the switching task. From another perspective, IAD subjects show impaired cognitive flexibilities.